The Columbia anthology of Yuan drama - Hsia, Chih-tsing, 1921-2013; Li, Wai-yee; Kao, George, 1912-2008 (Translations from the Asian classics., 2014)
This anthology features translations of ten seminal plays written during the Yuan dynasty (1279?1368), a period considered the golden age of Chinese theater. By turns lyrical and earthy, sentimental and ironic, Yuan drama spans a broad emotional, linguistic, and stylistic range. Combining sung arias with declaimed verses and doggerels, dialogues and mime, and jokes and acrobatic feats, Yuan drama formed a vital part of China's culture of performance and entertainment in the thirteenth and fourteenth centuries. To date, few Yuan-dynasty plays have been translated into English. Well-known.